Non-Candida albicans Candida species: virulence factors and species identification in India - Dharmendra Singh; Rajesh K Verma; Swati Sarswat; Satender Saraswat (Mazandaran University of Medical Sciences, 2021)
Background and Purpose: The predominant cause of candidiasis was Candida albicans which has recently changed to non-Candida albicans Candida (NCAC) (i.e., Candida spp. other than the C. albicans). The NCAC spp., earlier considered non-pathogenic or minimally virulent, are now considered a primary cause of morbidity and mortality in immunocompromised individuals. Given the NCAC spp.has become more common in clinical cases, this study aimed to determine the prevalence of NCAC spp. in different clinical specimens and assess a few of their virulence factors.Materials and Methods: Routine samples for bacterial culture and sensitivity that showed colony characteristics, like Candida on Blood Agar and microscopic features resembling Candida spp., were processed further. Candida isolates underwent tests for chlamydospore formation and biochemical tests, including sugar fermentation and sugar assimilation tests. These were grown at 42oC, and their colony color was identified using HiCrome™ Candida Differential Agar (HiMedia Laboratories Pvt. Ltd., Mumbai,India), HiCandidaTM Identification Kit (HiMedia Laboratories Pvt. Ltd., Mumbai, India),and VITEK-2® Compact (Biomérieux, France). Virulence factors, such as adherence to buccal epithelial cells (ABEC), biofilm formation, hemolytic activity, and production of coagulase enzyme were also tested.Results: Mean age of the patients was 38.46 years with a male-female ratio of 1.36:1. In total, 137 Candida isolates were recovered; 45.3%, 19.7%, and 13.9% of the isolates were isolated from urine, vaginal swabs, and oropharyngeal swabs, respectively. Moreover, 55(40.1%) isolates were those of C. albicans and 82 (59.9%) isolates belonged to NCAC spp.,with C. tropicalis (23.4%) contributing highest among NCAC species. Furthermore, C. albicans (3; 50%) was the most common spp. in cases of candidemia. Haemolysin production (85.5%) and ABEC (78.2%) were the major virulence factors in C. albicans. C.tropicalis (59.4%) and C. dubliniensis (50%) showed maximum ABEC. Biofilm forming capacity was higher in C. tropicalis (78.1%) than C. albicans (67%).Conclusion: Results of this study suggest varied prevalence and virulence based on geographical locations, even within a subcontinent. It clearly indicates the emergence of the NCAC spp. and their predominance in different body fluids. Identification of Candida to the spp. level should become a routine in all laboratories.